2018
DOI: 10.4103/ijpsym.ijpsym_187_17
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Burden in the Morbidly Obese in Multidisciplinary Bariatric Clinic in South India

Abstract: Background: Obesity is a global epidemic. Bariatric surgery is being considered as the treatment of choice in morbid obesity. Psychiatric comorbidity affects outcomes in this population. There is a dearth of data on psychiatric profile of the morbidly obese from Indian subcontinent. We studied people with morbid obesity to estimate the psychiatric burden among them and to identify factors associated for developing psychiatric disorders. Methodology: This is a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…In our study, the most prevalent associated diseases were hypertension, type 2 diabetes mellitus and psychiatric diseases, in agreement with the literature (21,23,25) . This comorbidity profile, commonly seen in obese patients, confers a greater risk of complications when there is a diagnosis of COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the most prevalent associated diseases were hypertension, type 2 diabetes mellitus and psychiatric diseases, in agreement with the literature (21,23,25) . This comorbidity profile, commonly seen in obese patients, confers a greater risk of complications when there is a diagnosis of COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…A study from Southern India on morbidly obese individuals suggested that about 30% of individuals attending an obesity clinic had psychological problems. 72 Recommendations for Counselling MNT and lifestyle interventions are likely to fail if patients are not kept sufficiently motivated throughout life. Hence, it is very important for physicians to understand their patients well and keep them motivated.…”
Section: Need For Counselling and Motivationmentioning
confidence: 99%
“…The health-related quality of life in severe obesity is worse in comparison to non-obese counterparts[ 264 ]. The psychiatric comorbidities in these patients are also high[ 265 ]. A formal psychological evaluation is suggested in the current guidelines[ 33 , 136 , 266 ].…”
Section: Psychological Assessmentmentioning
confidence: 99%